Wyburn–Mason syndrome presenting with bilateral retinal racemose hemangioma with unilateral serous retinal detachment - Bhanu P S Pangtey; Piyush Kohli; Kim Ramasamy (Indian Journal of Ophthalmology, 2018)
Wyburn–Mason syndrome is associated with unilateral retinal racemose hemangioma. Rarely, it presents with bilateral and symmetrical grade of malformation. We describe a 37-year old male, who presented with Wyburn–Mason syndrome presenting with bilateral but asymmetrical retinal hemangioma. The eye with advanced grade of hemangioma was complicated with exudation, intraretinal fluid, neurosensory detachment, and reduced vision. He was treated with one intravitreal injection of bevacizumab, after which both the intraretinal fluid and neurosensory detachment resolved. His vision improved and was maintained till 1 year of follow-up.